Asymmetric Information in the Interbank Foreign Exchange Market - Geir Høidal Bjønnes; Carol Osler; Dagfinn Rime (Norges Bank, 2008)
This paper provides evidence of private information in the interdealer foreign exchange market. In so doing it provides support for the hypothesis that information is an important reason for the strong positive correlation between order flow and returns. It also provides evidence that information influences order-book structure. Our data comprise the complete record of interdealer trades at a good-sized Scandinavian bank during four weeks in 1998 and 1999, including bank identities. Our results indicate that larger banks have more information than smaller banks, that the relation between order flow and returns is stronger for larger banks than smaller banks, and that larger banks exploit their information advantage in limit-order placement.
hdl:11250/2497760
Keywords: G15; F31; F33; 330; foreign exchange; microstructure; asymmetric information; liquidity premium